X-ray analysis of SDSS J165202.60+172852.4, an obscured quasar with outflows at peak galaxy formation epoch - Ishikawa, Yuzo; Goulding, Andy D; Zakamska, Nadia L; Hamann, Fred; Vayner, Andrey; Veilleux, Sylvain; Wylezalek, Dominika (Monthly notices of the Royal Astronomical Society, 2021)
We report on deep XMM-Newton and NuSTAR observations of the high redshift, z = 2.94, extremely red quasar (ERQ), SDSS J165202.60+172852.4, with known galactic ionized outflows detected via spatially resolved [O III] emission lines. X-ray observations allow us to directly probe the accretion disc luminosity and the geometry and scale of the circumnuclear obscuration. We fit the spectra from the XMM-NewtonlEPIC and NuSTAR detectors with a physically motivated torus model and constrain the source to exhibit a near Compton-thick column density of N-H = (1.02(-0.41)(+0.76)) x 10(24) cm(-2), a near edge-on geometry with the line-of-sight inclination angle of theta(i) = 85 degrees, and a scattering fraction of f(sc) similar to 3 per cent. The absorption-corrected, intrinsic 2-10 keV X-ray luminosity of L2-10= (1.4(-1)(+1)) x 10(45) erg s(-1) reveals a powerful quasar that is not intrinsically X-ray weak, consistent with observed trends in other ERQs. We also estimate the physical properties of the obscuration, although highly uncertain: the warm ionized scattering density of n(e) similar to 7.5 x (10(2)-10(3)) cm(-3) and the obscuration mass of M-obsc similar to 1.7 x (10(4)-10 (6))M-circle dot. As previously suggested with shallower X-ray observations, optical and infrared selection of ERQ has proved effective in finding obscured quasars with powerful outflow signatures. Our observations provide an in-depth view into the X-ray properties of ERQs and support the conclusions of severely photon-limited studies of obscured quasar populations at high redshifts.